Sistema de producción basado en la planificación de requerimiento de materiales (mrp) en la Empresa de Muebles de Madera “Álvarez” del cantón Santo Domingo - Urrutia Vargas, Paúl Eduardo (2019)
The present research project was carried out in the wooden furniture company "Álvarez", located in Santo Domingo canton, Province of Santo Domingo de Los Tsáchilas, the same one that aims to implement a material requirements planning system, for this, annual sales were identified, in which the main product was selected according to the criterion of greater demand and utility by means of the Pareto chart categorizing them into products A and B, following with an analysis of the processes by means of flowcharts for the obtaining of the finished product for a later planning of tasks by means of the interpretation of Gantt and Pert graphs. For the elaboration of the planning of material requirements, a forecast model was applied to estimate future sales, providing necessary information in the elaboration of the production plans, with which the production planning could be established during a semester in which it details the labor to be hired and investment costs, obtaining how the quantity to be produced per month results, which helped to determine the components to be acquired or manufactured for the calculation of the MRP. Keywords: Production, Materials, Sales, Forecast, Planning